Decarbonization pathways in Latin America: Assessing the economic and policy implications of transitioning to renewable energy sources - Thomas Stringer; Monserrat Ramírez-Melgarejo (Next Energy)
The Paris Agreement's ambitious target of limiting the global temperature rise to 1.5°C remains elusive, with the world falling short of its climate commitments. The electricity sector, responsible for a substantial 39% of global carbon emissions, plays a pivotal role in curbing climate change. Transitioning to renewable energy sources is not just an environmental imperative but also a pressing economic challenge, especially for governments tasked with financing renewable projects. This study explores the economic dimensions of decarbonizing electricity grids, shedding light on the costs and benefits. This research quantifies the costs of current fossil fuel-based electricity production versus achieving net-zero emissions across ten Latin American countries by evaluating annual electricity generation costs and estimating the expenses of transitioning to renewables. We find that decarbonizing these countries’ electricity grids would lead to annual savings close to USD 21 billion annually, potentially contributing positively to their economies. The study also compares the energy policies for each of the ten Latin American nations included, evaluating the role of renewable-oriented policies in decarbonizing power generation. We also find that policies vary in effectiveness across countries, and have to be in line with geographical constraints and economic realities.